Postmastectomy Breast Reconstruction Combined With Contralateral Breast Augmentation for Taiwanese Women With Small Breasts. (March 2017) - Liu, Hung-Hui; Chiang, I-Han; Wang, Chih-Hsin; Chiao, Hao-Yu; Chou, Chang-Yi; Wang, Chi-Yu; Tzeng, Yuan-Sheng; Chen, Tim-Mo; Chen, Shyi-Gen
Abstract : Background: Although autogenous tissue-based breast reconstruction has been widely used in the past decade, implant-based breast reconstruction is more often used in Taiwan because Asian women are generally slender with small breasts. For patients with very small breasts, it is hard to achieve the goal of reconstructing a similar breast to the contralateral one, even with the smallest size implant available commercially. Therefore, these patients need not only breast reconstruction but also contralateral breast augmentation. Here we report the surgical outcomes and cosmetic results of breast reconstruction using cohesive gel implants combined with simultaneous contralateral breast augmentation. Materials and Methods: A retrospective chart review was conducted to identify all patients with AA-sized to B-sized breast cups undergoing expander-implant reconstruction combined with contralateral breast augmentation between 2002 and 2015. Thirty patients were included. For each patient, patient profile (age, body mass index, and initial breast size), type and stage of breast cancer, surgical information (including implant sizes and the type of reconstruction and augmentation), and postoperative subjective pain scales were recorded. Outcomes were analyzed by identifying complications, the need for surgical revision, the presence of local or distant metastases, and patient satisfaction ratings. Results: At a mean 2.3-year follow-up (range, 4 months to 12 years), problems occurred in 7 of the 30 patients, with 9 complications in 8 reconstructed breasts and in 1 augmented breast. Complications were mostly capsule contracture. Aesthetic satisfaction was rated as "excellent" or "good" by most of the patients, and only 1 commented "poor" on both overall and reconstructed results because of postoperative radiotherapy-associated skin necrosis. The total mean subjective pain scale was 1.9/10; a higher mean pain scale of 3.08 was noted in those patients undergoing augmentation with no extra incision. Conclusions: This is the first report of implant-based breast reconstruction with simultaneous contralateral augmentation in Taiwan, showing its efficacy, safety, and good cosmetic outcomes with relatively low complication and revision rates.